Pelangi Persahabatan - Siti Alliena Rofi'ah; 1998; Syawallailanisa; 1997; Sahra Salsabila; Annisa Exsarika; 1999; Evania Ramadhanti; Deya Lina Rohana; Arva Salsa Ramadhanty; Tuty Damayanti; Rizky Akbari Putri; et al. (Leutikaprio, 2012)
Buku ini berisi kumpulan cerita pendek